DAMPAK PENGELUARAN PEMERINTAH DAN WISATAWAN SERTA INVESTASI SWASTA TERHADAP KINERJA PEREKONOMIAN BALI: SUATU SIMULASI MODEL SOCIAL ACCOUNTING MATRIX - ANTARA, MADE (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Bali's economic development is focused on agriculture, tourism and industry as the first priority. While other part of the Indonesia economy were suffering severely due to economic down turn since the middle of 1997, Bali's economy seems less affected. The performance of Bali's economy was analyzed employing 1996 Social Accounting Matrix (SAM), constructed based on 55x55 accounts. It is assumed that this 1996 SAM could represent the present situation of Bali's economy. The impact of increased allocation of expenditures for economic infrastructure, without increased in total government expenditure, on the performance of Bali’s economy was relatively low. While increased allocation of expenditure on social infrastructure or public services without increase in total government expenditure would deteriorate substantially the performance of Bali’s economy. Maintaining the government expenditure for development as in 1996 levels, but an increase in the expenditure of tourists or private investment, would enhanced the performance of Bali’s economy. Even a decline in government expenditure could be compensated by an increase in tourist expenditure or private investment, suggesting that government expenditure was not the main sources of economic growth. However, an increase in tourist expenditure without effort to increase the government expenditure would affect the income distribution among household group towards more inequality. But, increase tourist expenditure as well as government expenditure would promote better income distribution.
Keywords: SAM, Government Expenditure, Tourist Expenditure, Private Investmen, Performance of Bali’s Economy